Family Communication and Coping Strategies on Soldier Children’s Independence: A Maqasid Al-Shariah Perspective - Hartatiah Hartatiah; Akhmad Khalimy; Muh. Isra Bil Ali (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2025)
The dynamics of military families, characterized by high mobility and father absence due to operational duties, pose unique challenges to child development. This study aims to analyze the influence of family communication and coping strategies on the independence of soldiers’ children, viewed through the lens of Maqāṣid al-Sharī’ah. Using a mixed-method explanatory sequential design, quantitative data were collected from 200 respondents in the Kodam III/Siliwangi battalion, followed by in-depth interviews with selected informants. The results indicate that family communication and coping strategies significantly influence children’s independence, explaining 75.5% of the variance. The study theoretically contributes to Islamic Family Law by reframing psychological resilience as a spiritual necessity: effective communication is hifz al-nafs (preservation of the soul). At the same time, adaptive coping strategies manifest as hifz al-din (preservation of religion) and hifz al-nasl (preservation of progeny). Practically, these findings urge military institutions to integrate spirituality-based counseling into family support programs.